Autophagy-related microRNAs: Possible regulatory roles and therapeutic potential in and gastrointestinal cancers. (November 2020) - Pourhanifeh, Mohammad Hossein; Vosough, Massoud; Mahjoubin-Tehran, Maryam; Hashemipour, Maryam; Nejati, Majid; Abbasi-Kolli, Mohammad; Sahebkar, Amirhossein; Mirzaei, Hamed
Abstract: Gastrointestinal (GI) cancers with a high incidence rate and adverse complications are associated with severe morbidity and mortality around the world. It is well recognized that early detection of the disease results in longer survival rate and better quality of life. Autophagy, an intracellular regulatory process, has been shown to play an essential role in the pathogenesis of various malignancies including GI cancers. MicroRNAs (miRNAs) are small non-coding RNAs that have regulatory functions in tumor cells and possess potential diagnostic values in early detection of cancers. It has been recently demonstrated that these molecules have modulatory effects on multiple steps of autophagy process occurring in GI malignancies. In this review, we aimed to highlight the role of autophagy-related microRNAs on GI cancer as potential targets for cancer therapy.